Dental Mesenchymal Stem/Stromal Cells and Their Exosomes - Stanko, Peter (Stem Cells Int, 2018)
Stem cells derived from human dental pulp tissue (DP-MSC) differ from the other mesenchymal stem cells prepared from bone marrow or adipose tissue due to their embryonic origin from the neural crest and are of special interest because of their neurotropic character. Furthermore, the therapeutic potential of DP-MSCs is realized through paracrine action of extracellularly released components, for which exosomes play an important role. In this review, we intend to explore the properties of these cells with an emphasis on exosomes. The therapeutic applicability of these cells and exosomes in dental practice, neurodegenerative diseases, and many other difficultly treatable diseases, like myocardial infarction, focal cerebral ischemia, acute lung or brain injury, acute respiratory distress syndrome, acute inflammation, and several others is concisely covered. The use of cellular exosomes as an important diagnostic marker and indicator of targeted cancer therapies is also discussed, while the importance of stem cells from human exfoliated deciduous teeth as a source of evolutionally young cells for future regenerative therapies is stressed. We conclude that exosomes derived from these cells are potent therapeutic tools for regenerative medicine in the near future as clinical administration of DP-MSC-conditioned medium and/or exosomes is safer and more practical than stem cells.